Clinical validation of novel lightning dose optimizer for gamma knife radiosurgery of irregular‐shaped arteriovenous malformations and pituitary adenomas. Issue 8 (24th June 2022) - Pokhrel, Damodar; Bernard, Mark E.; Knight, James; St. Clair, William; Fraser, Justin F.
Abstract: Purpose: To demonstrate the clinical feasibility of a novel treatment planning algorithm via lightning dose optimizer (LDO) on Leksell Gamma Knife (LGK) GammaPlan with significantly faster planning times for stereotactic radiosurgery (SRS) of the complex and difficult arteriovenous malformations (AVMs) and pituitary adenomas. Methods and materials: After completing the in‐house end‐to‐end phantom testing and independent dose verification of the recently upgraded LDO algorithm on GammaPlan using the MD Anderson's IROC anthropomorphic SRS head phantom irradiation credentialing, 20 previously treated GK‐SRS patients (10 AVM, average volume 3.61 cm 3 and 10 pituitary adenomas, average volume 0.86 cm 3 ) who underwent manual forward planning on GammaPlan were retrospectively replanned via LDO. These pathologies were included because of the need for adequate dose delivery with organs at risk in very close proximity. LDO finds the target curvature boundary by well‐formulated linear programing objectives and inversely optimizes the GK‐SRS plan by isocenter placement, optimization, and sequencing. For identical target coverage, the LDO and original manual plans were compared for target conformity, gradient index, dose to critical organs, and surrounding normal brain. Additionally, various treatment delivery parameters, including beam‐on time were recorded. Results: For both patient cohorts, LDO provided similar target coverage with better dose conformity, tighter radiosurgical dose distribution with a lower value of gradient indices (all p  < 0.001), and lower dose to critical organs. For AVMs, there was a significant reduction of normal brain V 10Gy, V 12Gy, and V 14Gy by 4.74, 3.67, and 2.67 cm 3 (all p  < 0.001). LDO had twice the number of shots ( p  < 0.001), and longer beam‐on time ( p  = 0.012) by a factor of 1.44. For pituitary adenomas, LDO provided systematically lower values of V 10Gy, V 12Gy, and V 14Gy by 1.08, 0.86, and 0.68 cm 3 (all p  < 0.001), and lower maximum dose to optic pathway by 0.7 Gy ( p  = 0.005), but had almost twice the numbers of shots ( p  < 0.001) and increased beam‐on time ( p  = 0.005) by a factor of 1.2. However, for both patient groups, the average planning time for the LDO was <5 min, compared to the estimated 30–90 min of manual planning times. Conclusion: GK‐SRS treatment on Leksell Perfexion GammaPlan using the LDO provided highly conformal target coverage with a steep dose gradient, spared critical organs, and significantly reduced normal brain dose for complex targets at the cost of slightly higher treatment times. LDO generated high‐quality treatment plans and could significantly reduce planning time. If available, the LDO algorithm is suggested for validation and clinical use for complex and difficult GK cases.